A review of microencapsulation methods for food antioxidants: Principles, advantages, drawbacks and applications - Ozkan, Gulay; Franco, Paola; De Marco, Iolanda; Xiao, Jianbo; Capanoglu, Esra (Food chemistry, 2019)
•The protection of the bioactive compounds could be improved in the case of using carrier agents.•The technique and wall material have a great impact on the encapsulation characteristics.•The process parameters related with the physico-chemical functions of encapsulated materials should be optimized. Bioactivities and numerous health benefits against a number of oxidative stress related diseases have been attributed to the role of dietary antioxidants. The development of physical (spray drying, lyophilization, supercritical fluid precipitation and solvent evaporation), physico-chemical (coacervation, liposomes and ionic gelation) and chemical encapsulation techniques (interfacial polymerization and molecular inclusion complexation) enable to obtain healthier and acceptable bioactive compounds. This review focuses on the impacts of microencapsulation techniques on the encapsulation characteristics of food antioxidants. Additionally, this study also provides detailed information on the principles, effective parameters, advantages, disadvantages and applications of microencapsulation techniques.